Optimalisasi Program E-Peken dalam Pemberdayaan Masyarakat untuk Meningkatkan Produktivitas UMKM di Kota Surabaya - Syaputra, Andhika Ramadhan; Dida Rahmadanik; Ghulam Maulana Ilman (Public Sphere Review, 2025)
This study aims to analyze the impact of community empowerment through the E-Peken Program on increasing the productivity of Micro, Small, and Medium Enterprises (MSMEs) in Surabaya City. E-Peken is a locally developed digital platform designed to facilitate MSMEs in accessing online markets while enhancing business capacity through technical training and field mentoring. The research uses a qualitative approach with data collection methods including in-depth interviews with government officials, application managers, MSME users, and non-user community members. The results indicate that the E-Peken Program has significantly improved digital skills, business confidence, and market access for MSME participants. Intensive mentoring and a user-friendly system supported by a website and WhatsApp integration are key factors contributing to the program's success. However, the findings also reveal that public awareness of the program remains limited, preventing broader community involvement as potential consumers. Therefore, inclusive promotional strategies and greater community engagement are essential to optimize the program's effectiveness in enhancing MSME productivity and strengthening the local digital economic ecosystem.